Implementation of Plastic Bag Reduction by Communities and Businesses in Supporting the SDGs in Barru Regency - Samsimbar, Samsimbar; Nurlia, Nurlia (LPPPIPublishing, 2025)
This study aims to analyze the implementation of plastic bag reduction policies by communities and business actors in support of achieving the Sustainable Development Goals (SDGs) in Barru Regency. The research adopts a qualitative approach, utilizing data collection techniques such as interviews, observations, and documentation. The findings indicate that public awareness of the environmental impacts of plastic bag usage is increasing; however, challenges remain in maintaining consistent behavioral change and ensuring the availability of eco-friendly alternatives. Business actors show varying degrees of support depending on the type of business and their understanding of existing regulations. The local government has issued policies to promote plastic reduction, although enforcement and public outreach efforts are considered insufficient. The implementation of this policy contributes to the achievement of SDG Goal 12 (responsible consumption and production) and Goal 12 (climate action). Collaboration among the government, businesses, and communities is identified as a key factor in fostering behavioral transformation and creating a more sustainable environment.